Evaluation of the role of Islamic values in improvement of spiritual health among Iraqi Muslims - Wahyuni, W. (HTS teologiese studies, 2022)
Given that most of the adults’ life is spent in the workplace, and because the quality of working life has a significant effect on family life and community health, it is crucial to study the components involved in the improvement of the workplace and people’s health in the work environment. Therefore, by examining the common literature of Islamic values, spirituality and spiritual health, an attempt has been made in this research to explain organisational values and spiritual health in the management of organisations and to analyse the relationship of these variables with each other in Iraq using an Islamic approach. Similar to any other community, an Islamic community requires management proportional to its specific circumstances. In fact, an Islamic community needs a type of management that intertwines with divine and Islamic values and ethical principles and prioritises Islamic ideals. Therefore, this study aims to evaluate the role of organisational values in the improvement of Islamic values of Iraqi Muslims. To this end, 2800 employees selected from 30 oil and chemical compound manufacturing organisations are examined. According to the results, the Islamic values governing the Iraqi organisations play an effective role in the improvement of employees’ spiritual health.Contribution: Divine and religious values and Islamic ethics have always been considered in Islamic communities, where formal and informal procedures are taken into consideration. An Islamic approach to management is combined with Islamic values, behaviours and ethics, and these values affect Islamic administration. Therefore, a proper understanding of Islamic values will help develop the right plan for human resource management, as well as the maintenance of organisational and community health.